The Rise of Fund Managers in Foreign Exchange: Will Fundamentals Ultimately Dominate? - Thomas P. Gehrig; Lukas Menkhoff (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2004)
This paper analyzes the behaviour and motivation of fund managers in foreign exchange markets reflected in questionnaire evidence. We find that fund managers and FX dealers differ significantly. Fund managers rely more on fundamentals, basically due to their longer forecasting horizons, and reject non-fundamental influences on exchange rates more than FX dealers. However, neither can fund managers be considered as pure fundamentalists. Non-fundamentalist positions markedly influence short-term decision-making. They inspire ambivalent views about market imperfections and these views seem to become stronger over time. This latter change counterbalances the strengthening fundamental influences resulting from the rise of fund managers.
Keywords: G23; F31; 330; foreign exchange; market microstructure; fund management; fundamentals